2015
DOI: 10.1002/chin.201504266
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Review on Synthesis of Bioactive Pyrazoline Derivatives

Abstract: Review: 43 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Studies have shown that azachalcones possess anti-bacterial, anti-inflammatory, and anti-cancer properties [ 28 , 29 , 30 , 31 ]. Azachalcones also served as precursors for synthesis of pyrazolines and pyrazoles [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that azachalcones possess anti-bacterial, anti-inflammatory, and anti-cancer properties [ 28 , 29 , 30 , 31 ]. Azachalcones also served as precursors for synthesis of pyrazolines and pyrazoles [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The properties and applications of pyrazoline and their analogues are numerous and known, not only in the biological and medical field, [1][2][3][4] but also for their potential and practical applications as materials with luminescent and nonlinear optical properties. [5][6][7][8] The building of these N-heterocycles systems, from simple reactions, using small molecules and compatible with multicomponent, regioselective, eco-friendly and efficient synthetic procedures, which include variations to conventional methods, allows to incorporate specific structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Their usage in the treatment is attributed to their inherent toxicity to various pathogens 4 . Pyridine derivatives are an interesting class of heterocycles due to their synthetic versatility and effective biological activities such as antimicrobial 5 7 , anticancer 8 , anticonvulsant 9 , antiviral 10 , anti-HlV 11 , antimycobacterial and antifungal activities 12 .…”
Section: Introductionmentioning
confidence: 99%